Facts and fantasies : images of Istanbul women in the 1920s - Ture, Fatma (Cambridge Scholars Publishing, 2015)
The question of women and their rights was a prominent and ongoing topic of debate in the popular press of Turkey in the 1920s. This work presents an insightful analysis of those debates and follows its traces in obscene literature of the period, as a marginal, but influential branch of popular literature. Popular literature of the time carefully scrutinizes urban Istanbul women in particular, from their biological responsibilities to their behavior in the public arena, down to their clothe ...